Agriculture sector implications of a green economy transition in the Western Cape Province of South Africa : a system dynamics modelling approach to food crop production - Van Niekerk, Jacobus Bosman Smit (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.